Reading habit; reading culture; public library; librarian; Ankara; Turkey - Parviz F. Kazımi (Türk Kütüphaneciliği)
In this study, the importance of books and libraries in creating social and cultural environment by referring to historical events is pointed out. It is also emphasized that reaching reliable results based on the diverse resources regarding language, religion, ethnicity, genetics, geographical, archeological and ideological etc. is important.